Peningkatan Kompetensi Komunikasi Akademik Mahasiswa melalui Program Pelatihan Debat Bahasa Inggris dan Bahasa Arab - Bidari Widhi (Jurnal Kolaboratif Sains, 2026)
Academic communication competence is an essential skill that university students need to succeed in learning, research, and future professional careers. However, preliminary observations revealed that many students experienced difficulties in participating in English and Arabic debating competitions, including limited academic vocabulary, weak argumentation skills, low self-confidence, insufficient grammatical competence, and limited understanding of debate formats. This community service program aimed to enhance students' academic communication competence through an English and Arabic debate training program. The program employed a participatory approach consisting of lectures, workshops, debate simulations, group practice, intensive mentoring, and participant performance evaluation. The participants were university students preparing for regional and national debate competitions. Evaluation was conducted through observation, performance assessment, and continuous feedback during the training sessions. The results indicated significant improvements in students' speaking ability, academic argument construction, debate techniques, self-confidence, critical thinking, and teamwork. Participants also demonstrated a better understanding of debate procedures and were able to present arguments more logically, systematically, and persuasively. The program provided meaningful experiential learning and contributed to strengthening students' academic communication competence. Furthermore, it established the foundation for a sustainable debate community that can continuously prepare students for academic debate competitions at various levels.